Externally-imposed soil movement effects on piles - Goh, Anthony Teck Chee. (2008)
The main objective of this study was to gain a better understanding of the interaction between the moving soil and the oile around it and to investigate the limiting soil pressures acting on single piles and pile groups as well as the relevant parameters influencing the behaviour of piles subjected to lateral soil movements.